2006
DOI: 10.1038/sj.embor.7400645
|View full text |Cite
|
Sign up to set email alerts
|

The role of glutathione in disulphide bond formation and endoplasmic‐reticulum‐generated oxidative stress

Abstract: Glutathione is a ubiquitous molecule found in all parts of the cell where it fulfils a range of functions from detoxification to protection from oxidative damage. It provides the main redox buffer for cells and as such has been implicated in the formation of native disulphide bonds. However, the discovery of the enzyme Ero1 has called into question the exact role of glutathione in this process. In this review, we discuss the arguments for and against a role for glutathione in facilitating disulphide-bond forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
289
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(306 citation statements)
references
References 32 publications
(51 reference statements)
3
289
0
2
Order By: Relevance
“…Third, GSH may play an important role in oxidative protein folding that is disrupted as a result of 17-AAG blockade of Hsp90 chaperoning functions. Recent studies have shown that GSH is required to regulate formation of certain native disulfide bonds, thereby contributing to correct folding of substrate proteins (47). When this process is disrupted due to endoplasmic reticulum stress, which may occur as a result of ansamycin treatment, reactive oxygen species may be released from the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Third, GSH may play an important role in oxidative protein folding that is disrupted as a result of 17-AAG blockade of Hsp90 chaperoning functions. Recent studies have shown that GSH is required to regulate formation of certain native disulfide bonds, thereby contributing to correct folding of substrate proteins (47). When this process is disrupted due to endoplasmic reticulum stress, which may occur as a result of ansamycin treatment, reactive oxygen species may be released from the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we note that reported estimates of HeLa cell volume (2;600 μm 3 ) (23) and typical concentrations of cellular reduced glutathione (ca. 5 mM) (24) suggest that PL is present at quantities greatly in excess of cellular glutathione under our assay conditions (1,000 cells per well, 50 μL per well). As such, direct conjugation of PL with glutathione at C3 is a plausible explanation for the observed decrease in total glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous protein production often results in the accumulation of reactive oxygen species (ROS) due to an increased demand for protein folding in the ER (23). The ROS accumulation in Y1EK was set as 1 relative fluorescence unit (RFU) (Fig.…”
Section: Figmentioning
confidence: 99%